Burocracia y tiempo como actores en el proceso de decisión. La sucesión del gran duque de Alba en el gobierno de los Países Bajos - Wolf, J. G. C. de (Cuadernos de Historia Moderna, 2003)
This paper studies the decision making process at the beginnig of the Dutch Revolt from the arrival of the Duke of Alba to his replacement by Luis de Requesens (1566-1573). Its aim is analyse the administrative and political difficulties that had influence in the election of the man more appropiate to face up to the repression of the rebels, to finance the cost of the war and to get the support of these provinces. A bad weather, the factional rivalry at the court of Philip II and the resistance of the elites involved in this conflict were determinant in this decision making process.